2016
DOI: 10.1212/wnl.0000000000002963
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging overuse is more common in Medicare compared with the VA

Abstract: Objective: To inform initiatives to reduce overuse, we compared neuroimaging appropriateness in a large Medicare cohort with a Department of Veterans Affairs (VA) cohort.Methods: Separate retrospective cohorts were established in Medicare and in VA for headache and neuropathy from 2004 to 2011. The Medicare cohorts included all patients enrolled in the Health and Retirement Study (HRS) with linked Medicare claims (HRS-Medicare; n 5 1,244 for headache and 998 for neuropathy). The VA cohorts included all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In the National Ambulatory Medical Care Survey (NAMCS), neurologist visits were associated with increased neuroimaging (3). However, within the Veterans Administration system, neuroimaging rates for patients with headache is lower when compared to Medicare patients; although it is unclear whether neurologist input into the imaging decisions or other system factors explain these differences (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the National Ambulatory Medical Care Survey (NAMCS), neurologist visits were associated with increased neuroimaging (3). However, within the Veterans Administration system, neuroimaging rates for patients with headache is lower when compared to Medicare patients; although it is unclear whether neurologist input into the imaging decisions or other system factors explain these differences (33).…”
Section: Discussionmentioning
confidence: 99%
“…14 , 15 Nevertheless, several studies focused on the use of individual low-value health services (eg, prostate cancer screening and colonoscopy) have demonstrated that the delivery of low-value care still occurs at VAMCs. 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Nevertheless, several studies focused on the use of individual low-value health services (eg, prostate cancer screening and colonoscopy) have demonstrated that the delivery of low-value care still occurs at VAMCs. 3,[16][17][18][19][20][21][22] As health care costs continue to increase and recent legislation provides veterans with increasing flexibility regarding whether they receive care within or outside the VHA, quantifying the frequency and patterns of low-value care delivery is essential for the VHA to reduce wasteful health care spending without compromising quality or patient satisfaction. 15,23 Our objective was to characterize the frequency of and VAMC-level variation in the delivery of low-value care, with a focus on low-value diagnostic testing for 4 common conditions in the VHA.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical practice guidelines for neuroimaging in headache have been widely distributed, challenges continue to emerge regarding cor-rect identification of patients requiring neuroimaging. For instance, a study evaluating appropriate neuroimaging in headache suggested that while patients with headache may be receiving fewer inappropriate neuroimaging tests, these patients may also be receiving fewer appropriate neuroimaging tests (Burke et al, 2016). Furthermore, roughly 9% of patients assessed in the ED with nonspecific, transient, or mild symptoms are misdiagnosed and not appropriately evaluated for CVA.…”
Section: Discussionmentioning
confidence: 99%